Effectiveness of a predator avoidance program for elementary-aged youth - Smith, Matthew Lee; LoPilato, Alexander C.; Bergeron, Caroline D. (Frontiers in Public Health, 2024)
Introduction With thousands of children abducted and abused each year, efforts are needed to keep children safe from predators. Revved Up Kids (RUK) is an intervention that gives elementary-aged children the necessary tools to recognize and avoid dangerous people and situations. The purposes of this study were to describe the RUK intervention components and document its effectiveness. Methods This evaluation utilized a quasi-experimental design to determine the effectiveness of RUK. The single-session intervention was offered in two formats: one-hour (n = 119 youth) and three-hour (n = 28 youth) workshops. RUK workshop effectiveness was compared to a comparison group (n = 211 youth) that did not receive an intervention. Data were collected at baseline, immediate-post, and 1-month follow-up from second to fourth grade participants. A series of linear mixed models were fitted. Results Compared to the comparison group, participants in both RUK workshops showed significant improvements across the three time points. More specifically, participants in the one-hour and three-hour RUK workshops significantly increased their safety knowledge measured by the Recognize Score (p < 0.01), Avoid Score (p < 0.01), and Escape Score (p < 0.01), respectively. Discussion These effective single-session workshops can be easily introduced into schools and community-based settings to complement existing efforts to prevent child abduction and abuse.